Gasto público social y pobreza en Ecuador, periodo 2007 - 2020 - Faican Cuenca, Kevin Ronaldo (2023)
Poverty is a problem faced by all countries, in Latin America the quality of life and their rights are affected or violated, largely due to the scarcity of basic goods and services to live. The general objective of this study is "To analyze the amount invested in public social spending and its impact on poverty in Ecuador in the period 2007-2020. The quantitative method was used by estimating two econometric models, simple linear regression and multiple linear regression between variables, in order to identify the relationship between public spending and poverty during the period 2007-2020. The data were obtained from official information issued by the National Institute of Statistics and Census (INEC), the Economic Commission for Latin America and the Caribbean (ECLAC) and the Ministry of Economy and Finance of Ecuador. The results showed that public spending showed continuous growth and a decrease in multidimensional poverty during the study period, in addition to being inversely correlated, with a high level of dependence on public social spending, resulting in a correlation coefficient (Rho) of - 93.8%. In conclusion, it was possible to identify that public social spending comprises an average of 23.88% of Ecuador's Gross Domestic Product, and its impact on poverty is significant with a p-value < 0.05 with a corrected R^2 of 73.5%, which contributes to poverty reduction, the average amount of investment is 7.4 billion (4 billion in education, 2.6 billion in health, and 800 million in urban development and housing), decreasing by 14.66 percentage points.